2021
DOI: 10.1007/s41109-021-00374-7
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories through temporal networks

Abstract: What do football passes and financial transactions have in common? Both are networked walk processes that we can observe, where records take the form of timestamped events that move something tangible from one node to another. Here we propose an approach to analyze this type of data that extracts the actual trajectories taken by the tangible items involved. The main advantage of analyzing the resulting trajectories compared to using, e.g., existing temporal network analysis techniques, is that sequential, temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…This includes other community currencies 6,16,17,21 as well as major global cryptocurrencies 19,20,26,40 . Recent methodological advances 10,52 promise to extend applicability also to payment systems that are not themselves full currency systems, such as mobile money systems 10,53,54 , large value payment systems [55][56][57][58][59][60][61] , major banks 12,[62][63][64] , and, in an exciting development, centralized national payment infrastructures [65][66][67] or central bank digital currencies 68 . Modern economic infrastructure makes detailed observation possible, and the circulation of money can be studied as (interconnected) networks of monetary flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes other community currencies 6,16,17,21 as well as major global cryptocurrencies 19,20,26,40 . Recent methodological advances 10,52 promise to extend applicability also to payment systems that are not themselves full currency systems, such as mobile money systems 10,53,54 , large value payment systems [55][56][57][58][59][60][61] , major banks 12,[62][63][64] , and, in an exciting development, centralized national payment infrastructures [65][66][67] or central bank digital currencies 68 . Modern economic infrastructure makes detailed observation possible, and the circulation of money can be studied as (interconnected) networks of monetary flow.…”
Section: Discussionmentioning
confidence: 99%
“…However, modern payment infrastructure is increasingly digital 5 , and the circulation of money is leaving real-time records on the servers of financial institutions worldwide. These transaction records offer especially high granularity in time and in space, and open up the possibility of fined-grained data-driven studies of financial ecosystems [6][7][8][9][10][11][12] . In this paper we consider the question of how best to study the circulation of money as observed in transaction records.…”
Section: Introductionmentioning
confidence: 99%
“…That the observation period extends well into the COVID-19 pandemic is especially relevant, as community currencies tend to have higher utility during economic and/or financial crises 1 , 3 , 4 , 19 , 25 , 27 . More broadly, this dataset serves as a detailed account of an innovative digital currency system of relevance to research topics like digital and financial inclusion 28 32 or informal credit and insurance arrangements 15 , 26 , 33 , 34 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Datasets such as the one described in this paper allow for empirical observation at higher granularity 1 , 39 – 42 with the potential to inform modelling of currencies and payment systems 43 – 47 . Financial transactions are also an example of real-world walk processes on networks; this dataset will support the development of novel techniques for temporal network analysis 32 , 48 . It will be of particular interest for studying economic networks, where transaction data could be used to explore the relation between network topology, trading dynamics, and allocation of resources 34 , 49 54 .…”
Section: Background and Summarymentioning
confidence: 99%
See 1 more Smart Citation